Rahasia shalat dalam mencegah perbuatan keji persperktif Syekh Ibnu ‘Athaillah dalam Kitab Tajul ‘Arus - Fathul Jannah; Nikmah Royani Harahap; Apriliana (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
The purpose of this study is to see how far the prayer is applied and measured in the life of the day, and to see the effect or clear evidence that a servant feels after he has completed his prayer. This study uses the method of descriptive-analysis, which is a procedure of problem solving studied by describing the state of the subject / object of study, which later in this study the researchers will reveal the understanding of Ibnu 'Athaillah about the secret of prayer in preventing evil deeds. The steps that the researchers used in this study were librarian studies. (Libraray Reserach). Penliit aggregates both primary data, namely the title book of the current, and other supporting data. The result of this study shows that there is still a number of Muslims today who perform the prayer only ceremonial, so that those who perform this prayer bnayak who do not feel the great secret of prayer that he feels, that is, prevent himself from evil deeds.